PENERAPAN WORK PREPARATION DAN INTENSITAS PENDAMPINGAN PADA CAPAIAN PRESTASI PRAKTIK PEMESINAN MAHASISWA JURUSAN MESIN FAKULTAS TEKNIK UNIVERSITAS NEGERI YOGYAKARTA - Thomas Sukardi (LPMPP Universitas Negeri Yogyakarta, 2010)
Abstract: Work Preparation and Coaching Intensity to Improve MechanicalEngineering Students Academic Achievement in the Machinery Practicum in theEngineering Faculty of the Yogyakarta State University. This study aims to revealthe effects of the work preparation and coaching system for mechanical engineeringstudents of the Engineering Faculty of the Yogyakarta State University on the 3rdMachinery Practicum. This study was a classroom action research study. Thepopulation comprised all the students and the sample consisted of 19 3rd semesterstudents. The data were collected through questionnaires, observations, anddocuments and analyzed by quantitative and qualitative descriptive techniques.The results are as follows. 1) The work preparation and coaching system ran welland was conducted in 10 weeks (2 cycles). The work preparation was made by thestudents before the class started. They consulted the lecturer 10 minutes before. Thecoaching was effective if it was carried out every 30 minutes since that class started.2) The students passed this practicum if they obtained a score of 78.15 andsuccessfully finished 5 of 7 jobs. 3) The process ran well and the students showed agood attitude towards work and worked seriously.Keywords: work preparation, coaching intensity